If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5 = 7g + 4 Reorder the terms: 5 + 3y = 7g + 4 Reorder the terms: 5 + 3y = 4 + 7g Solving 5 + 3y = 4 + 7g Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3y = 4 + -5 + 7g Combine like terms: 5 + -5 = 0 0 + 3y = 4 + -5 + 7g 3y = 4 + -5 + 7g Combine like terms: 4 + -5 = -1 3y = -1 + 7g Divide each side by '3'. y = -0.3333333333 + 2.333333333g Simplifying y = -0.3333333333 + 2.333333333g
| n^2-n-180=0 | | 2x+49=9x-5 | | 7x-5=10(3) | | 12-3(x+2)=x+8 | | 2a-1b=200 | | 21y-2=9 | | 3x+5=-29-8x | | x^2-66x+216=0 | | 15y-10-8+6y=9 | | 15x-10-8+6y=9 | | 2x-2=10-50 | | 2y-5y=17solvey | | 3x+50=6x+26 | | 2y-5y=7 | | .75z=-3 | | 10x+6=2x-I | | 8+8n+15-3n=33 | | 14(x+3)=7+5 | | 9-9x=159-44x | | 9-9x=158-44x | | 4(4x-4)+3x=15 | | 3(4+5)+8=25 | | 2c-11c=12 | | -(x+1)-5=0 | | 2(3y-7)+6y=5 | | 30=-5(6x+5) | | 14x+2x-6x-9x=20 | | 16a+7c+5-7a+1=22 | | -14=-3+t | | 8*-15-6y=-10 | | 6x+2+3x+6q=17 | | 3(3x+4)-6(4-x)=33 |